Birokrasi di negara birokratis : makna, masalah, dan dekonstruksi birokrasi Indonesia - Said, M. Mas'ud. (Malang : UMM Press, 2007)
Bureaucracy in Indonesia.
Includes bibliographical references and index.
Keywords: Deconstruction -- Political aspects -- Indonesia; Bureaucracy -- Indonesia